Biochemical and microbiological activity of soil contaminated with o-cresol and biostimulated with Perna canaliculus mussel meal - Zaborowska, Magdalena (Environ Monit Assess, 2018)
The choice of the study subject was a consequence of the growing interest in volatile organic compounds which are strongly dispersed in the environment. The knowledge of o-cresol’s capability for being broken down by bacteria should be supplemented by studies aimed at determining the biochemical and microbiological activity of soils. o-Cresol was applied at the following rates: 0, 0.1, 1, 10, and 50 mg of o-cresol kg(−1) d.m. of soil to determine its effect on the biological properties of soil. The activity of dehydrogenases, catalase, urease, acid phosphatase, alkaline phosphatase, arylsulfatase, and β-glucosidase, the eight groups of microorganism counts, was determined in soil samples after 45 days and the barley yield was determined. Preventive biostimulation with Perna canaliculus mussel meal, illustrated by means of the index of fertility (IF), was conducted in order to eliminate the adverse effect of o-cresol. The soil and crop resistance index (RS) was used to illustrate the response of barley, and R:S—the rhizosphere effect index was used to determine the effect of the crop on the enzymatic activity of soil. o-Cresol had a beneficial effect on the biological activity of soil at an acceptable rate of 0.1 and 1 mg kg(−1) d.m. of soil, and it became its inhibitor after being applied at 10 and 50 mg kg(−1) d.m. of soil, which also brought about a decrease in the resistance of spring barley. Dehydrogenases are the most sensitive, and catalase is the least sensitive, to the pressure of o-cresol in soil. Mussel meal can be recommended as a biostimulator of soil fertility. It also eliminated the negative effect of o-cresol on its biological activity.